Predicting pressure distribution between transfemoral prosthetic socket and residual limb using finite element analysis. (2016) - Surapureddy, Rajesh; Schönning, Alexandra; Stagon, Stephen; Kassab, Alain
A static implicit nonlinear finite element model (FEM) was created and analysed to determine the pressure distribution between the residual limb and the prosthetic socket of a transfemoral amputee. This analysis was performed in an attempt to develop a process allowing healthcare providers and engineers to simulate the fit and comfort of transfemoral prosthetics to reduce the number of re-fittings. The FEM considered the effects of donning and body weight and included geometric nonlinearity due to large deflections, nonlinear contacts due to friction, and nonlinear hyper-elastic material properties for the residual limb's soft tissue. The results attained can provide prosthetic fitting clinicians customised information on where the prosthetic fits too tight, and how stress concentrations would change as a result of geometric modifications to the prosthetic. This knowledge can improve patients' comfort levels by providing well targeted and more accurate modifications to the prosthetic, minimising the need for numerous refittings.